PENGARUH APLIKASI PINTAR JEPANG TERHADAP PENGUASAAN KOSA KATA BAHASA JEPANG SISWA KELAS XII SMK NEGERI 1 TELUK KUANTAN - Sella Amalya; Nana Rahayu; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This study aims to determine whether the Smart Japanese application has an effect on increasing the Japanese language vocabulary of class XII students at SMK Negeri 1 Teluk Kuantan. The sample used was 40 students. The research that will be carried out in this research is quantitative research. This research will be carried out with a Pre Test and Post Test Control Group design. The class will be divided into an experimental class and a control class. The experimental class will be given treatment using the Smart Japan application, while the control class will only study as usual. The data used for this study were taken from the scores of the experimental class and the control class. After the data is obtained, the data will be processed using SPSS Version 20 IBM For Windows. For the scores of the experimental class and the control class, a p-value of 0.000 was obtained, which means that Ho was rejected and Ha was accepted, or it can be concluded that there was a significant difference in the average score between the experimental class and the control class. From the explanation above, it can be concluded that the learning media for the Smart Japanese application vocabulary has an effect on the mastery of Japanese vocabulary for class XII students at SMK Negeri 1 Teluk Kuantan.Key Words: Influence, Vocabulary, Smart Japanese